Evaluation of Serum Levels of Trace Elements, Malondialdehyde, Ceruloplasmin in the Development of Preeclampsia - Shaikh Mahmood, Syed Shabbar Masih, Syyeda Anees (International Journal of Innovative Research in Medical Science, 2016)
Preeclampsia is a pregnancy-specific condition that increases maternal and fetal mortality and morbidity. Despite its prevalence and severity, the patho-physiology of this multisystem disorder is poorly understood and its etiology has not yet been fully elucidated. This study was aimed to evaluate the role of trace elements copper, zinc, magnesium, antioxidant ceruloplasmin (Cp) and lipid peroxidation product malondialdehyde (MDA) in the pathogenesis of preeclampsia. The results showed increased levels of serum copper, Cp and MDA in normal pregnant women (group II) and in pregnant women with preeclampsia (group III) when compared to normal non pregnant women (group I), ( P< 0.001). Further these levels were higher in group III when compared to group II (P< 0.001). Serum levels of zinc were significantly decreased in group II when compared to group I (P< 0.001) and were significantly lower in group III when compared to group II (P< 0.001). There was no significant difference in serum magnesium levels in controls and cases (P= 0.2927). The findings suggest that lipid peroxidation along with imbalance of antioxidants of micronutrients may be an important factor in the pathogenesis of preeclampsia.